Simultaneous quantification of endothelin receptor antagonists and phosphodiesterase 5 inhibitors currently used in pulmonary arterial hypertension - Enderle, Yeliz; Witt, Lukas; Grünig, Ekkehard; Haefeli, Walter E.; Burhenne, Jürgen (Journal of pharmaceutical and biomedical analysis, 2017)
Combination treatment with endothelin receptor antagonists (ERA) and phosphodiesterase 5 inhibitors (PDE5I) improved efficacy of pulmonary arterial hypertension (PAH) therapy. However, drug-drug interactions, variable exposure, non-adherence can influence plasma levels. For these reasons, drug quantification may be advantageous particularly in patients with poor treatment responses. We developed, validated, and applied an assay for the simultaneous quantification of ambrisentan, bosentan, macitentan, sildenafil, and tadalafil as well as their main (and partly active) metabolites in human plasma. This method is based on LC-MS/MS separation for a rapid and sensitive quantification with stable isotopically labelled analogues as internal standards for each drug and metabolite. Sample preparation was carried out using a solid phase extraction protocol based on Oasis HLB material. The separation was achieved on a Kinetex C18 column and multiple reaction monitoring in negative ionization mode was used for sensitive detection. The calibrations were linear for all analytes with correlation coefficients >0.99 within the concentration range observed under a therapeutic PAH dosing scheme with lower limits of quantification between 0.34ng/mL (OH-ambrisentan) and 10ng/mL (despropyl-macitentan). Intra- and inter-day precision at LLOQ and QC levels ranged between 2.03% and 19.8%, and 0.65% and 14.0%, respectively. The sample turnover time was 12min. The applicability of this versatile LC/MS/MS assay was verified by the successful analysis of clinical routine samples of patients on PAH medication. This new method allows for the first time to assess trough drug and metabolite levels of the currently approved PDE5I and ERAs in PAH patients, thus enabling for measurement of samples in clinical routine.